2015
DOI: 10.3109/00365521.2015.1095352
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy of culture-based tailored therapy forHelicobacter pylorieradication with that of the traditional second-line rescue therapy in Korean patients: a prospective single tertiary center study

Abstract: Tailored therapy based on H. pylori culture and MIC test could be an option as a second-line eradication regimen in the presence of high level of antimicrobial resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(61 citation statements)
references
References 30 publications
1
59
0
1
Order By: Relevance
“…Figure 1 details the procedure of study selection in the flow chart. Thirteen studies [13][14][15][16][17][18][19][20][21][22][23][24][25] were qualified in this meta-analysis. Tables 1 and 2 set 2 different control groups, respectively, which were labeled as group a and b in our study (e.g., Lee a and Lee b).…”
Section: Statistical Analysesmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 1 details the procedure of study selection in the flow chart. Thirteen studies [13][14][15][16][17][18][19][20][21][22][23][24][25] were qualified in this meta-analysis. Tables 1 and 2 set 2 different control groups, respectively, which were labeled as group a and b in our study (e.g., Lee a and Lee b).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Ten tailored regimens [14][15][16][17]19,[21][22][23][24][25] were designed according to pretreatment susceptibility testing (pooled RR ¼ 1.17, 95% CI 1.11-1.24). Three other studies 13,18,20 advanced their susceptibility-guided therapy by additionally adjusting their PPI administration (either by dosage adjustments or by changing drugs) on the basis of CYP2C19 polymorphism (pooled RR ¼ 1.14, 95% CI 1.01-1.28).…”
Section: Types Of Tailored Regimensmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a study has shown that antimicrobial susceptibility-guided therapy is more effective than empiric concomi- Patients that completed study protocol (n = 60) tant therapy with fewer adverse effects (28). The superiority of a tailored therapy as a second-line approach was also demonstrated by a South-Korean prospective study (29). Furthermore, it may also prove to be a cost-effective strategy in high clarithromycin resistance regions (30,31).…”
Section: Discussionmentioning
confidence: 99%